THE EFFECT OF NIGELLA SATIVA (BLACK CUMIN) SEED EXTRACT ON CANDIDA ALBICANS VIABILITY - DARMAWAN, WULAN; FARIDA, RATNA; REDJEKI, SRI (International Journal of Applied Pharmaceutics, 2019)
Objective: Nigella sativa has antifungal effects against Candida albicans. The antifungal activity of N. sativa is due to the components of thymoquinone, thymol, and carvacrol. Oral candidiasis is a common opportunistic infection of the human oral cavity typically caused by the infection of C. albicans. The aim of this study was to assess the antifungal effectiveness of N. sativa seed extract (SE) on the viability of C. albicans. Methods: C. albicans was added to the wells of 96-well microtiter plates that were coated with artificial saliva and exposed to N. sativa SE at concentrations of 6.25%–50% or 1 μl of amphotericin B (250 mg/μl) as a positive control. The viability of C. albicans was determined with the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. Results: The optical density of C. albicans incrementally decreased on exposure to increasing concentrations of N. sativa SE. Conclusion: N. sativa SE concentration is inversely correlated to the viability of C. albicans.